2010
DOI: 10.1590/s1519-566x2010000500018
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de genótipos de tomateiro e de extratos aquosos de folhas de Melia azedarach e de sementes de Azadirachta indica sobre Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae)

Abstract: -Insecticide plants are an important tool among the new alternatives for pest control in IPM systems because they reduce the use of synthetic insecticides, preserving human health and the environment. We investigated the effects of aqueous extracts of Melia azedarach leaves and Azadirachta indica seeds and three tomato genotypes, 'Santa Clara', 'IPA-5' -Solanum lycopersicum (= Lycopersicon esculentum Mill), and LA444-1 -S. peruvianum (= L. peruvianum), on the development, reproduction and longevity of the toma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Mixtures were maintained in sealed flasks for 24 h for the extraction of water soluble compounds, and after this period were filtered through fine fabric (voile), obtaining the 5% aqueous extracts (BRUNHEROTTO et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Mixtures were maintained in sealed flasks for 24 h for the extraction of water soluble compounds, and after this period were filtered through fine fabric (voile), obtaining the 5% aqueous extracts (BRUNHEROTTO et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Mahmoud, Soliman, Abdel-Moniem, & Abdel-Raheem (2013) examined the lethal effects of emamectin benzoate on the larvae of cotton bollworm, Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae), and found that the insecticide caused a significant decline in the population of pest. The effect of azadirachtin was investigated on different stages Comparative Lethal and Sublethal Toxicity of Some Conventional Insecticides of the T. absoluta, and the highest lethal effect was shown on the larval stage of this pest (Branherotto & Vendraim, 2010). The lethal effects of imidacloprid, phenoxycarb, fentoat, thiocyclam, and dinotefuran were studied on T. absoluta larvae and the highest and the lowest lethal percentages were recognized with imidacloprid and phenoxycarb, respectively (Eman, Redwan, & Hanan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite two fruiting periods per year by the neem tree, their unavailability throughout the year limits the use of seed-based preparations. Interestingly, numerous active compounds including limonoids have also been found in neem leaves (Siddiqui et al, 2000) and leaf extracts had been shown to exert insecticidal effects against several insect pest species (Brunherotto et al, 2010;Egwurube et al, 2010). The choice of neem was made from literature but more importantly from the traditional practices of local gardeners in Togo.…”
Section: Introductionmentioning
confidence: 99%